Adsorção do corante azul de metileno na rama de mandioca (Manihot esculenta crantz) - Freitag, Juliana Alves (2013)
The dyes are generally applied in various industry sectors, are used in food, pharmaceutical, textile and paper. The methylene blue dye is commonly used in the production of paper and other materials such as polyesters and nylons. Some basic dyes exhibit biological activity and are used as antiseptics. The methylene blue present in the composition the structure of the phenothiazine compound is present in antihistamines, and antipsychotics. When heated methylene blue can generate sulfur oxide and nitric oxide and cause toxicological effects in aquatic organisms and water quality. So often there are new studies related to the treatment of these effluents. The adsorption in biomass has proved a profitable option for the treatment of wastewater containing dyes or other pollutants, itis a technical simple and low cost since it does not require high initial investment. Following this context, the present study investigated the adsorption of methylene bluedye in raw cassava. The biomass was characterized by the determination of moisture and ash. Adsorption studies were conducted in a batch system at room temperature. The parameters evaluated were: pH, ionic strength, contact time and adsorption isotherm. The optimum pH for the adsorption of Methylene Blue in raw cassava were 5 e 8. In the study of ionic strength proved that the increase ofionic strength of the solution decreases the efficiency of adsorption. The Langmuir isotherm model was the best adapted to the experimental data, showing better linearity (R ² = 0.986) when compared to the Freundlich model (R ² = 0.956) using the Langmuir model can also calculate that the maximum adsorption capacity was 90.1 mg.g-1qmax. Values were found close to other biomass as adsorbents studied in the literature. Thus the raw cassava presented himself as a good adsorbent in the adsorption of the dye methylene blue.